2005
DOI: 10.1161/01.hyp.0000164571.77710.19
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Type 2 Receptor–Mediated Phosphorylation of eNOS in the Aortas of Mice With 2-Kidney, 1-Clip Hypertension

Abstract: Abstract-To evaluate the role of vascular angiotensin II (Ang II) type 2 (AT 2 ) receptor in renovascular hypertension, we investigated expressions of AT 2 receptor and endothelial nitric oxide synthase (eNOS) in thoracic aortas of mice with 2-kidney, 1-clip (2K1C) hypertension. The mRNA levels of AT 2 receptor in aortas, but not those of AT 1 and bradykinin B 2 receptors, increased 14 days but not 42 days after clipping. The contractile response to Ang II (Ͼ0.1 mol/L) was attenuated in aortic rings excised 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
61
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 29 publications
11
61
0
3
Order By: Relevance
“…[31][32][33] The mRNA for AT 2 receptors is upregulated in the aorta of mice with early 2K,1C hypertension. 34 Moreover, AT 2 receptor activation limits aortic contractions to Ang II in this model by phosphorylation of endothelial NOS and increasing vascular cGMP. 34 NO generation in the clipped kidney may account for our finding that blockade of AT 1 or AT 2 receptors or NOS apparently prevented any further fall in the CBF of clipped kidneys with enalaprilat ( Figure 2A).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[31][32][33] The mRNA for AT 2 receptors is upregulated in the aorta of mice with early 2K,1C hypertension. 34 Moreover, AT 2 receptor activation limits aortic contractions to Ang II in this model by phosphorylation of endothelial NOS and increasing vascular cGMP. 34 NO generation in the clipped kidney may account for our finding that blockade of AT 1 or AT 2 receptors or NOS apparently prevented any further fall in the CBF of clipped kidneys with enalaprilat ( Figure 2A).…”
Section: Discussionmentioning
confidence: 84%
“…34 Moreover, AT 2 receptor activation limits aortic contractions to Ang II in this model by phosphorylation of endothelial NOS and increasing vascular cGMP. 34 NO generation in the clipped kidney may account for our finding that blockade of AT 1 or AT 2 receptors or NOS apparently prevented any further fall in the CBF of clipped kidneys with enalaprilat ( Figure 2A). This confirms the conclusions of Beierwaltes and colleagues 20,35 that the RBF of the clipped kidney of early 2K,1C renovascular hypertensive rats is highly dependent on NOS, although this effect wanes with time.…”
Section: Discussionmentioning
confidence: 84%
“…29 Additionally, expression of the AT2 receptors within the heart under normal conditions is extremely low; however, during hypertension, its expression increases to the degree that its action predominates over that of the AT1 receptors. 32 AT2R messenger ribonucleic acid (mRNA) is upregulated in the aorta of mice with early 2K1C hypertension, 33 and AT2R activation limits Ang II-induced aortic contractions in 2K1C hypertensive rats (via the phosphorylation of endothelial NO synthase and the increased production of vascular cGMP). 33 Thus, the increased expression of AT1 receptors and the decreased expression of PD123319-sensitive receptors in the normotensive rats in comparison to that in the 2K1C hypertensive rats may be responsible for the alamandine's pressor effect that was observed in the normotensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…32 AT2R messenger ribonucleic acid (mRNA) is upregulated in the aorta of mice with early 2K1C hypertension, 33 and AT2R activation limits Ang II-induced aortic contractions in 2K1C hypertensive rats (via the phosphorylation of endothelial NO synthase and the increased production of vascular cGMP). 33 Thus, the increased expression of AT1 receptors and the decreased expression of PD123319-sensitive receptors in the normotensive rats in comparison to that in the 2K1C hypertensive rats may be responsible for the alamandine's pressor effect that was observed in the normotensive rats. 29, 33 It is possible that alamandine's pressor effect masks the depressor response in normotensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…3 A large body of evidence has shown that nitric oxide (NO) production is increased as a buffer against hypertension in two-kidney one-clip (2K-1C) hypertensive animal models. [4][5][6] The increase in NO production that is observed in several vascular beds from 2K-1C hypertensive animals may not completely prevent high blood pressure but could serve as a protective vascular mechanism that contributes to the preservation of the erectile function in this model. 7 Insulin-like growth factor-binding protein-3 (IGFBP-3) is a member of the insulin-like growth factor (IGF) family.…”
Section: Introductionmentioning
confidence: 99%